Substantiation of the algorithm for controlling the adjustable electric drive of roller crusher-grinders of forage grain - M. A. Pryshchepau; V. A. Daineko; A. M. Pryshchepava (Аграрная наука Евро-Северо-Востока)
In recent years, along with the traditional technology of dry grain storage and grinding before feeding, the technology of preserving crushed grain at an early stage of ripeness is widely used. These technologies do not replace each other, but objectively complement each other, that is, they exist in parallel and require appropriate equipment for their implementation. To do this, it is necessary to use universal energy-efficient equipment for crushing feed grain with a high annual load. As such equipment, it is advisable to use roller crusher-grinders with individual electric drive of the rollers. The process of crushing and grinding grain is significantly affected by the physical and mechanical properties of the grain and the design and technological parameters of roller crusher-grinders. Analysis of the strength properties of the grain shows that in order to reduce the energy intensity the process of crushing the grain must be carried out at a higher moisture content and the deformation rate should be as high as possible. When a certain circumferential speed of the rollers is reached, the process reaches both maximum performance and minimum energy consumption. The control algorithm is based on changing the speed of the rollers stepwise from a lower speed to a higher one. In this case, at each stage a metered portion of grain is crushed between the upper and lower flaps of the vertical loading shaft, and the time by which this portion will have been worked out is measured. This procedure is carried out by changing the speed from lower to higher until the speed at which crushing of the portion will take the minimum time is determined. If the technological process requires a grain grinding mode, the speed of one of the rollers increases from the optimal crushing rate. The speed increase occurs as long as the recu-peration current in the parallel-connected DC buses of the frequency converters increases.